Spinal cord stimulation trial can control pain caused by chronic limb-threatening ischemia - Yuta Terabe (JPRAS Open)
Background: Patients with chronic limb-threatening ischemia experience long-duration pain during ulcer treatment. Hence, painkillers are gradually increased, but adverse events often occur. Spinal cord stimulation trial is one of the methods used to manage such pain. Method: The study was performed at the Limb Salvage Center in Kasukabe Chuo General Hospital. Total 41 patients with mean age 70.4 ± 9.58 years underwent spinal cord stimulation trial for 2 weeks. Among them, 33 (80 %) were male, and 8 (20 %) were female. Numerical rating scores, wound results, spinal cord stimulation-related adverse events, and total dose of oral painkillers were evaluated. Results: Postoperatively, itching and bleeding were reported. The numerical rating scores improved from 7/10 before to 2/10 at 2 days after the spinal cord stimulation (P < 0.001). The total doses of oral painkillers showed no change before and after spinal cord stimulation (P > 0.05). Conclusions: Spinal cord stimulation is recommended for peripheral artery disease because it can improve numerical rating scores for a short term. Therefore, this trial approach can sufficiently control pain against chronic limb-threatening ischemia, without undergoing implantation.